What Determines the Reservation Wages of Unemployed Workers? New Evidence from German Micro Data - Eswar S. Prasad (Institute for the Study of Labor (IZA), 2003)
This paper provides new empirical evidence on the relationship between reservation wages of unemployed workers and macroeconomic factors – including aggregate and local unemployment rates, generosity of the unemployment compensation system and characteristics of the wage structure – as well as individual-specific determinants, including proxies for general and specific human capital, length of unemployment spell and alternative income sources. The longitudinal aspect of the dataset (the German Socio-Economic Panel) provides an interesting perspective on how reservation wages change over time and how they correlate with accepted wage offers for workers who make the transition from unemployment to employment. The findings have important policy implications as well, since they shed some light on the disincentive effects of the German tax and transfer system for the labor supply and employment decisions of unemployed workers at different points of the skill/offer wage distribution.
Keywords: J3; J6; 330; reservation wage; labor supply disincentives; offer wage distribution; unemployment and employment determinants; Arbeitslosigkeit; Lohn; Anspruchslohn; Arbeitsangebot; Schätzung; Deutschland